Incomplete markets and parental investments in children - Brant Abbott (Queen's University, Department of Economics, 2021)
The effect of incomplete markets on parental investments is investigated. Uninsured risk and credit constraints can distort the timing of parental investments, causing them to be delayed relative to what would occur under full-insurance. Age-dependent subsidies, taxes or transfers can all possibly correct this. Analytical results are provided, and a numerical life-cycle model provides quantitative results. Data on ability and parental investment dynamics are used to calibrate the model. A sequence of optimal policy experiments is conducted beginning with a simple reform of the tax and transfer schedule and ending with more complex parent-specific tax parameters and investment subsidies, all of which vary with child age. The final experiment generates substantial improvements in the ability distribution and a consumption equivalent welfare gain that is 2.5 times as large as simply reforming the tax schedule. About 1/4 of this incremental gain results from including childage dependent policies that alleviate distortions of parental investment timing.
Keywords: E2; E24; J24; 330; Incomplete Markets; Human Capital; Skill Formation